Integrated Metabolomics and Transcriptome Revealed the Effect of Fermented Lycium barbarum Residue Promoting Ovis aries Immunity - Zhang, Yajun; Guo, Yansheng; Luo, Yulong; Du, Min; Yin, Xin; Xu, Xiaochun; Zhang, Guijie (Frontiers in Immunology, 2022)
Lycium barbarum residue contains abundant bioactive nutrients which can be used as feed supplement. This study investigated the effects of fermented and non-fermented Lycium barbarum residues (RFW and RW) on the meat quality and immunity of sheep (Ovis aries). Fifty-four Tan sheep were randomly divided into control, RFW or RW treatments. Data showed that RFW and RW increased the carcass weight, fat content, ash content and reduced the cooking loss of lamb. RFW performed more significant effects on activating immune-related genes than those of RW. The expression of chemokines and immune-related pathways, such as signaling pathways of interleukin-17 signaling pathway and NOD-like receptor signaling pathway, were elevated in sheep fed RFW. RW increased the diversity in rumen metabolites, especially compositions of lipids, organic acids and organ heterocyclic compounds. RFW affected numerous compounds which are closely correlated with the activation of immune genes. In conclusion, RFW could represent a valuable strategy to improve growth performance and immunity of sheep.